Pedagogy: Implementation of the “Hong Ik In Ngan” Values Learning for Korean Learnes - Eo, Yoon Kyung; Nuryani, Pupun; Hikamudin, Eviana; Solahudin, M. Nizan (International Conference on Elementary Education, 2024)
This article discusses the pedagogical meaning of implementing "Hong Ik In Ngan" value learning for Korean students. The purpose of this writing is to find out and understand the meaning of character education in learning the values of "Hong Ik In Ngan" for Korean students. Apart from that, it is necessary to know how the process of implementing learning the values of "Hong Ik In Ngan" for students Korea, and the final reflective effort of implementing the learning values of "Hong Ik In Ngan towards Korean students. The method used in this writing is qualitative, with a literature study approach (library study) in this writing looking for sources related to problems and titles taken both primary and secondary. Therefore, this writing is intended to describe the content and content contained in the character of education, which is related to the values of "Hong Ik In Ngan", and the process of implementing the values of "Hong Ik In Ngan" for Korean students, as well as looking at reflective efforts, as assessing the benefits of implementing this learning for students, so that the values of "Hong Ik In Ngan" which are the source and foundation of Korean society's life, can be applied and embodied in everyday life for Korean students.